A new efficient distributed computing middleware based on cloud micro-services for HPC - Benchara, Fatema Zahra; Youssfi, Mohamed; Bouattane, Omar; Ouajji, Hassan (2016 5th International Conference on Multimedia Computing and Systems (ICMCS), 2016)
The aim of this paper is to present a new distributed computing middleware for High Performance Computing (HPC) based cloud micro-services. The great challenge is to maintain the scalability and efficiency of massively parallel and distributed computational system when the intensive big data processed by its applications is widely increased. Besides, the proposed middleware implements a new cooperative micro-services team works model for massively parallel and distributed computing. This model is constituted by distributed micro-services as Micro-service Virtual Processing Units (MsVPUs) with integrated load balancing service and an AMQP communication protocol that grant HPC. The paper shows the proposed distributed computational scheme and its integrated middleware accompanying by some experimental results.